Synthesis and photophysical properties of dansyl-based polyamine ligands and their Zn(II) complexes - Parola, A. Jorge (2007)
The synthesis, potentiometric studies and photophysical properties of two new polyamine ligands (L1 and L2) possessing the dansyl chromophore were studied in aqueous 0.15 M NaCl. The compounds show the absorption and emissions bands characteristic of the dansylamide fluorophore and both present intramolecular excited state proton transfer at intermediate pH ranges. One of the ligands (L2) strongly coordinates Zn(II) leading to fluorescence quenching. A model compound (L3) of the dansyl moiety was also investigated.